Association between colonoscopy and colorectal cancer occurrence and mortality in the older population: a population-based cohort study - Lee, Ji Young; Cha, Jae Myung; Yoon, Jin Young; Kwak, Min Seob; Lee, Hun Hee (Endoscopy, 2025)
We aimed to evaluate the association between colonoscopy and colorectal cancer (CRC) occurrence and related mortality in an older population.This retrospective, nationwide, population-based cohort study used data of adults aged ≥40 years from the Health Insurance Review and Assessment Service database. After excluding colonoscopy within 6 months of CRC diagnosis during enrollment, CRC occurrence and related mortality were compared between colonoscopy and non-colonoscopy groups using a time-dependent Cox proportional hazard model. Subgroup analysis was conducted among four age groups: young, middle-aged, old, and very old.Among 748986 individuals followed for 9.64 (SD 0.99) years, the colonoscopy group had a 65% lower CRC occurrence (adjusted hazard ratio [HRa] 0.35, 95%CI 0.32–0.38) and 76% lower CRC-related mortality (HRa 0.24, 95%CI 0.18–0.31) after 5 years compared with the non-colonoscopy group. Colonoscopy was associated with the most significant reduction in CRC occurrence in the middle-aged group (HRa 0.32, 95%CI 0.29–0.35) and in CRC-related mortality in the young group (HRa 0.04, 95%CI 0.01–0.33); the very old group had the least reduction in both CRC occurrence and CRC-related mortality (HRa 0.44, 95%CI 0.33–0.59 and HRa 0.28, 95%CI 0.15–0.53, respectively).We found a significant association between colonoscopy and reduction in CRC occurrence and CRC-related mortality in adults aged ≥40 years after 5 years of follow-up; however, these associations were weaker in the very old group. More research is needed on the association between colonoscopy and older age.